Mechatronic System Based on Bluetooth Communication with a Mobile Application for Automatic Irrigation in Greenhouses - Tasayco, Juan; Villanueva, Anthony; Yauri, Ricardo (Ital Publication, 2025)
Non-automatic irrigation in greenhouses presents significant disadvantages, such as waste of water and loss of time, although they are highly widespread and low cost. Research highlights the importance of rationally managing and using water through information technologies to improve crop quality, recommending the use of automated irrigation systems, although challenges are faced in the proper integration of electronic devices in agricultural environments. For this reason, it is considered that the use of drip irrigation, the integration of embedded systems with Bluetooth connection, and mobile applications facilitates its use. This paper describes the design and implementation of a prototype mechatronic system to manage greenhouse irrigation, using an embedded system based on a microcontroller. In this case, temperature and humidity sensors are used that control a water pump, monitor environmental factors, and display data in the mobile application connected via Bluetooth, activating the water pump automatically. The results show that the prototype is functional, meets the stated objectives, and proposes improvements related to the range of Bluetooth communication and the implementation of a solar panel for use in areas without electricity supply. Doi: 10.28991/ESJ-2025-09-01-02 Full Text: PDF